Anti-HIV-1 activity and structure–activity-relationship study of a fucosylated glycosaminoglycan from an echinoderm by targeting the conserved CD4 induced epitope - Lian, Wu; Wu, Mingyi; Huang, Ning; Gao, Na; Xiao, Chuang; Li, Zi; Zhang, Zhigang; Zheng, Yongtang; Peng, Wenlie; Zhao, Jinhua (Biochimica et biophysica acta, 2013)
Fucosylated glycosaminoglycan (FG) is a novel glycosaminoglycan with a chondroitin sulfate-like backbone and fucose sulfate branches. The aim of this study is to investigate the mechanism and structure–activity relationships (SAR) of FG for combating HIV-1 infection. Anti-HIV activities of FGs were assessed by a cytopathic effect assay and an HIV-1 p24 detection assay. The biomolecule interactions were explored via biolayer interferometry technology. The SAR was established by comparing its anti-HIV-1 activities, conserved CD4 induced (CD4i) epitope-dependent interactions and anticoagulant activities. FG efficiently and selectively inhibited the X4- and R5X4-tropic HIV-1 infections in C8166 cells with little cytotoxicity against C8166 cells and PBMCs. Our data indicated that FG bound to gp120 with nanomolar affinity and may interact with CD4i of gp120. Additionally, the CD4i binding affinity of FG was higher than that of dextran sulfate. SAR studies suggested that the unique sulfated fucose branches account for the anti-HIV-1 activity. The molecular size and present carboxyl groups of FG may also play important roles in various activities. Notably, several FG derivatives showed higher anti-HIV-1 activities and much lower anticoagulant activities than those of heparin. FG exhibits strong activity against X4- and R5X4-tropic HIV-1 infections. The mechanism may be related to targeting CD4i of gp120, which results in inhibition of HIV-1 entry. The carboxyl group substituted derivatives of FG (8.5–12.8kDa), might display high anti-HIV-1 activity and low anticoagulant activity. Our data supports further the investigation of FG derivatives as novel HIV-1 entry inhibitors targeting CD4i. [Display omitted] •A fucosylated glycosaminoglycan (FG) shows anti-HIV-1 activity with no cytotoxicity.•The FG can bind to gp120 with nanomolar affinity.•The FG may bind to the CD4 induced epitope region of the gp120.•The unique sulfated fucose branches of FG may account for its anti-HIV-1 activity.•Molecular size and chemical groups show different effects on the anti-HIV activities.